2010
DOI: 10.1177/0743558410371126
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Launch, Failure to Achieve Criteria for Adulthood?

Abstract: In the West it is not until the mid-20s or 30s people reach an adult status. Becoming an adult signifies being independent from others (especially from parents) and learning to stand alone as a self-sufficient person. This study investigates whether the attainment of such individual qualities are affected by emerging adults' living circumstances. Results indicate that though independent living is associated with an accelerated achievement of certain criteria for adulthood, continued coresidence with parents du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 43 publications
9
88
2
4
Order By: Relevance
“…As discussed earlier, this lower level of life satisfaction among unmarried solo residents in comparison to married family coresidents was in line with previous research on the positive relationship between marriage and wellbeing (Liu and Umberson 2008;Sassler and Schoen 1999). Young adults living alone, however, were likely to enjoy more life satisfaction than were their unmarried counterparts living with family members, as is the case in Western societies (Galambos and Krahn 2008;Kins and Beyers 2010). …”
Section: Life Satisfactionsupporting
confidence: 75%
See 3 more Smart Citations
“…As discussed earlier, this lower level of life satisfaction among unmarried solo residents in comparison to married family coresidents was in line with previous research on the positive relationship between marriage and wellbeing (Liu and Umberson 2008;Sassler and Schoen 1999). Young adults living alone, however, were likely to enjoy more life satisfaction than were their unmarried counterparts living with family members, as is the case in Western societies (Galambos and Krahn 2008;Kins and Beyers 2010). …”
Section: Life Satisfactionsupporting
confidence: 75%
“…A body of research conducted in Western societies has shown that living alone is positively related to wellbeing among young adults. For young adults, especially for those in their late teens and early 20s, gaining a sense of self and the social identity of being an independent adult is a major developmental task that needs to be accomplished (Jordyn and Byrd 2003;Kins and Beyers 2010). In Western societies, leaving the parental home often initiates a transitional process towards adulthood, followed by other role transitions, such as completing education, starting a career, and getting married and having children (Aassve, Arpino, and Billari 2013;Spéder, Murinkó, and Settersten Jr. 2014).…”
Section: Solo Living In Young Adulthoodmentioning
confidence: 99%
See 2 more Smart Citations
“…too early or too late, are thought to be the target of negative social sanctions and to experience psychological strain (Heckhausen, 1999;Salmela-Aro, 2009). For example, early transitions (such as early school leaving) and problems in establishing oneself in the labour market, have been associated with lower levels of life satisfaction and health (Kins & Beyers, 2010;Schulenberg, Bryant, & O'Malley, 2004).…”
Section: The Transition From School To Workmentioning
confidence: 99%